Profil Keterampilan 4C Guru Bimbingan dan Konseling SMP di Kota Makassar: Implikasinya dalam Manajemen Bimbingan dan Konseling di Abad 21 - Azzahrah, Humairah; Suherman, Uman; Syahril, M Fiqri (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
In the 21st-century education era, the 4C skills (critical thinking skill, creativity skill, collaboration skill, and communication skill) serve as the primary keys in guidance and counseling management within schools. The research objective is to analyze the 4C skill profile of guidance and counseling teachers in Makassar City Middle Schools and its implications for guidance and counseling management. A descriptive suvery method was utilized by gathering data from 60 guidance and counseling teachers through a multidimensional 4C skills questionnaire that had been validated by material experts, and also based on the model's suitability with confirmatory factor analysis, demonstrating good validity and reliability. The research findings indicate that the 4C skills of Makassar City Middle School guidance and counseling teachers are significantly high, with critical thinking variables in the high category, creativity in the very high category, collaboration in the high category, and communication in the high category. Thus, they can manage complex situations, design innovative programs, facilitate effective collaboration, and enhance communication effectively. Consequently, guidance and counseling teachers equipped with 4C skills enhance the quality of guidance and counseling management, as well as the achievement of educational success in schools.